Slim for life : my insider secrets to simple, fast, and lasting weight loss - Michaels, Jillian (New York : Harmony Books, 2013)
"Biggest Loser" trainer Jillian Michaels offers a no- nonsense, insider's plan to stop battling your weight and slim down for life.
Includes bibliographical references (p. 249-254) and index.
Adult.
Keywords: Physical fitness; Weight loss -- Popular works; Reducing diets -- Recipes; Nutrition -- Popular works